2020
DOI: 10.1063/5.0012124
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic piezoelectricity in (K,Na)NbO3-based lead-free single crystal: Piezoelectric anisotropy and its evolution with temperature

Abstract: Searching for lead-free piezoelectric materials with a large piezoelectricity and excellent thermal stability has been a major concern in both scientific research and practical applications. To understand the mechanism of high piezoelectricity and its temperature-dependent behavior in lead-free materials, we focus here on the tetragonal (K,Na,Li)(Nb,Ta)O3 single crystal and investigate the intrinsic d33* along arbitrary directions as well as its evolution with temperature. The synergistic influence of several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Based on the (110), (200), and (222) XRD peaks, the tetragonal unit cell parameters are calculated to be a = b = 3.9920 Å, and c = 4.0009 Å. In spite of the low T C , the KTN crystal demonstrates large tetragonal lattice distortion with c / a ‐1~0.0089, slightly lower than (K, Na, Li)(Nb, Ta)O 3 ( T C ~235℃) 6 and Pb(Nb 2/3 Mg 1/3 )O 3 ‐0.39PbTiO 3 ( T C ~177°C) 29 single crystals with high Curie temperature. Thus the reduced T C does results in a decreased tetragonality.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on the (110), (200), and (222) XRD peaks, the tetragonal unit cell parameters are calculated to be a = b = 3.9920 Å, and c = 4.0009 Å. In spite of the low T C , the KTN crystal demonstrates large tetragonal lattice distortion with c / a ‐1~0.0089, slightly lower than (K, Na, Li)(Nb, Ta)O 3 ( T C ~235℃) 6 and Pb(Nb 2/3 Mg 1/3 )O 3 ‐0.39PbTiO 3 ( T C ~177°C) 29 single crystals with high Curie temperature. Thus the reduced T C does results in a decreased tetragonality.…”
Section: Resultsmentioning
confidence: 97%
“…[1][2][3][4][5] Owing to the large piezoelectric coefficient and the excellent composition tunable property, the alkali niobate system, such as (K, Na)NbO 3 , KNbO 3 , etc., has been considered as the most promising lead-free candidate. [6][7][8][9][10] Saito et al and Wu et al have demonstrated that partial substitution of Ta for Nb could significantly improve the piezoelectricity of alkali niobate system. 11,12 The higher electronegativities of Ta compared to Nb were expected to make the alkaline niobate-based perovskite more covalent, which would benefit the improvement in piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, differences were observed in their descending behaviors. The R–O–T sample showed much lower small signal d 33 temperature stability compared with T and O–T samples, which may be donated by its low T C of 238 °C, [ 50 ] as listed in Figure S5 in the Supporting Information. Through the comparative analysis between small signal d 33 temperature stability and unipolar strain temperature stability, contrary to the benign unipolar strain stability, the R–O–T sample exhibited the worst small signal d 33 temperature stability.…”
Section: Resultsmentioning
confidence: 99%
“…A key solution to reduce the consumption of fossil fuels is to harvest this waste energy because 500 million tons of standard coal could be saved, which will reduce 1.31 billion tons of CO 2 emissions. The thermoelectric effect that makes a direct conversion between thermal and electrical energy, possesses a high potential in the waste heat harvesting field, exhibiting excellent characteristics including good stability, no pollution, high repeatability, low cost, compared to solar cells, wind nanogenerator, and piezoelectric devices. In the thermal–electrical field, a key parameter to evaluate the conversion efficiency is the unitless figure of merit ( ZT ), see eq where S , σ, T , and k are the Seebeck coefficient (V/K), the electric conductivity (S/m), the current absolute temperature of the material (K), and the thermal conductivity (W/m·K), respectively. It demonstrates that improving the performance of a thermoelectric generator need to increase electric conductivity, Seebeck coefficient, and decrease thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%